Structural, Energetic, and UV−Vis Spectral Analysis of UVA Filter 4‑tert-Butyl-4′-methoxydibenzoylmethane - Pinto da Silva, Luis (2014)
The growing awareness of the harmful effects of ultraviolet (UV) solar radiation has increased the production and consumption of sunscreen products, which contain organic and inorganic molecules named UV filters that absorb, reflect, or scatter UV radiation, thus minimizing negative human health effects. 4-tert-Butyl-4′-methoxydibenzoylmethane (BMDBM) is one of the few organic UVA filters and the most commonly used. BMDBM exists in sunscreens in the enol form which absorbs strongly in the UVA range. However, under sunlight irradiation tautomerization occurs to the keto form, resulting in the loss of UV protection. In this study we have performed quantum chemical calculations to study the excited-state molecular structure and excitation spectra of the enol and keto tautomers of BMDBM. This knowledge is of the utmost importance as the starting point for studies aiming at the understanding of its activity when applied on human skin and also its fate once released into the aquatic environment. The efficiency of excitation transitions was rationalized based on the concept of molecular orbital superposition. The loss of UV protection was attributed to the enol → keto phototautomerism and subsequent photodegradation. Although this process is not energetically favorable in the singlet bright state, photodegradation is possible because of intersystem crossing to the first two triplet states.